2018
DOI: 10.3389/fimmu.2018.01543
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Genetic Variations in Surfactant Protein D in Mycobacterial Infection and Their Association With Tuberculosis

Abstract: Surfactant proteins (SPs)-A and -D are C-type lectins of the collectin family and function in the clearance of infectious particles in the lungs. Some polymorphisms of SPs that give rise to amino acid changes have been found to affect their function. Several SP-A gene polymorphisms have been reported to be associated with respiratory infection diseases, such as tuberculosis (TB). However, the relationship between surfactant proteins D (SP-D) polymorphisms and TB is still unclear. To study the associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
(47 reference statements)
0
16
0
1
Order By: Relevance
“…This is the first definitive observation of conglutinin pattern recognition and binding to a Gram-positive bacterium (e.g., mycobacteria). SP-D has also recently been shown to bind to M. bovis BCG (36). The mycobacterial ligand for conglutinin is likely to be those reported for SP-D and M. tuberculosis , namely the terminal dimannosyl units of lipoarabinomannan (LAM) (37, 38), since SP-D is structurally similar to conglutinin (2) and M. bovis BCG shares an almost identical bacterial surface, including LAMs (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first definitive observation of conglutinin pattern recognition and binding to a Gram-positive bacterium (e.g., mycobacteria). SP-D has also recently been shown to bind to M. bovis BCG (36). The mycobacterial ligand for conglutinin is likely to be those reported for SP-D and M. tuberculosis , namely the terminal dimannosyl units of lipoarabinomannan (LAM) (37, 38), since SP-D is structurally similar to conglutinin (2) and M. bovis BCG shares an almost identical bacterial surface, including LAMs (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have studied the association between SPD polymorphisms and COPD susceptibility; this association was first reported in the Mexican population in 2001 26. Some studies have reported that the SPD gene plays an important role in the development of asthma 15, silicosis 27 and tuberculosis 28. However, there is still controversy concerning the genetic associations of SPD with COPD at present.…”
Section: Discussionmentioning
confidence: 99%
“…SP-A and SP-D polymorphisms are known to be associated with susceptibility to TB disease 44 . In fact, in a case-controlled study of 364 patients with TB and 177 control subjects in Taiwan, the SP-D 92T homozygous genotype was found to be a risk factor for TB 45 . In vitro assays further supplemented this finding by demonstrating that this variant had a lower binding ability to Mycobacterium bovis as well as a lower capacity to inhibit phagocytosis, resulting in less inhibition of intracellular growth of M. bovis 45 .…”
Section: Additional Effector Mechanisms Modulating the Establishment mentioning
confidence: 99%